The Muslim Brotherhood in Kuwait - Alkandari, Ali A. author. aut Link
XIII, 276 p. 15 illus., 12 illus. in color.
Keywords: The Muslim Brotherhood (MB) is the most influential, organized, social, and political movement in Kuwait. With the succession in Kuwait, the role of the organisation become more interesting for people interested in Kuwait and Gulf domestic politics as well as those interested in the MB and Political Islam. This book traces the emergence and development of MB while considering the political and social development of Kuwait that led to its appeal. It explains the evolution of MB’s organisational structure and how it adapted itself during different periods in Kuwait’s history through the Social Movement Theory. It describes MB policies and strategies during challenging times. It traces the circumstances surrounding the emergence of the MB and focuses on its development and its mobilisation strategy. It is certainly one of the first focused studies on MB from its conception in 1941 up to 1991. Ali Alkandari is an Associate Professor at the History Department of KuwaitUniversity. He did his MA and Ph.D. in History at Georgetown University and the University of Exeter, respectively. He is a political activist and has campaigned to support the opposition in Kuwait and support justice, freedom of speech, public education as a common good, and communities’ role in policy reform. He has appeared in numerous TV shows and interviews for his views.